PENGGUNAAN METODE ABJAD JARI DAN BAHASA TUBUH SERTA MEDIA PEMBELAJARAN DALAM PEMBELAJARAN PAI BAGI ANAK BERKEBUTUHAN KHUSUS TUNARUNGU DI SLB NEGERI MUSI RAWAS - Yuliansyah Yuliansyah (IAIN Bengkulu, 2018)
This research aims to describe the use of methods of the alphabet thumb and body language in learning islamic religious education on child tunarugu, and a utilization media learning in learning islamic religious education on child tunarugu and to know factors factor inhibitors and the utilization of media supporters learning in learning islamic religious education on child tunarugu. The research is descriptive research qualitative and is field research (field research). But technique data col- lection uses the observation, interview, and documentation. To analyse data using reduction data, presentation of data and the withdrawal of conclusion, checking the validity of data using triangulation. The result showed 1) use the alphabet fingers and body language in learning islamic education had gone well, because this method suitable for children with special needs disabled athletes tunarugu and students got the this method, 2) the use of media learning used in learning religious education in using media focus, media pictures outboard (posters), reading books and exercise pictures letters hijaiyah. And media letters hijaiyah card, 3) supporting factors media uses learning that education teachers who are willing to make media learning, the interest and the motivation to study students because medium used will attract learning, and the other facilities support. But factors that does not support is limited of education facilities and infrastructure, the absence of special teachers islamic educa- tion, students who have limited so it takes the old process in learning, lack of the guidance and motivation learn from parents or guardian students to his son.